Institutionalized inequity in the USA: The case of postdoctoral researchers. (6th December 2018) - Gaughan, Monica; Bozeman, Barry
Abstract: Coalitions of powerful higher education stakeholders, a weak federal government, controversial overlapping policy domains, and a vulnerable postdoctoral labor force combine to create exploitative conditions in the United States. Recent calls for postdoctoral reform are likely to fall by the wayside, just as they have for the last half century. We use several analytic tools to examine the situation: a thematic content analysis of National Academy of Science reports dating back to 1969, stakeholder analysis based on the content analysis, and an in-depth demographic assessment of the postdoctoral labor force. We use these data in concert with agenda-setting theory to explain why major change has not occurred, and is unlikely to occur in the future. We suggest that one way forward is for the federal government to engage in bureaucratic reforms, which are more politically insulated than the domains of science, education, immigration, and inclusion policies in the USA.